Reading Objects in the Contact Zone - Troelenberg, Eva-Maria (Heidelberg Studies on Transculturality, 2021)
The cultural effects of globalization constitute one of the most important challenges for the discipline of art history today. The aim of this publication is to take a critical look at art historical narratives. Based on transcultural object biographies, the volume brings together analyses of objects and images that circulate in transcultural contact zones: their histories of origin, circulation and perception slice through space and time. The histories of these objects and images thus demonstrate in exemplary fashion how knowledge and understanding can be generated, communicated or also challenged in cultural contact zones. Hence, the publication is designed as a methodological contribution to a transcultural art and cultural history. It is also conceived as an instrument for teaching and contains a critical-discursive glossary of key-terms that combines theory and practice of transcultural art history.